On the formation, structure and decay of a monsoon cyclonic storm near Delhi - A case study (MAUSAM, 1980)
The structure of a monsoon cyclonic storm formed near Delhi on 18 August 1976 has been studied with available data and the factors which led to its rapid intensification and decay have been discussed. There seems to be some structural difference, particularly in upper levels, in storms when they lie over sea than when they lie deep inland. The surface features of the storm as assessed from the autographic records of Delhi have also been presented in this paper.